The Oxford handbook of applied Bayesian analysis - O'Hagan, Anthony; West, Mike, 1959- (Oxford handbooks., 2010)
"Exploring contemporary Bayesian analysis across a variety of application areas, chapters written by leading exponents of applied Bayesian analysis showcase the scientific ease and natural application of Bayesian modelling, and present solutions to real, engaging, societally important and demanding problems. The Handbook is grouped into five general areas: Biomedical & Health Sciences; Industry, Economics & Finances; Environment & Ecology; Policy, Political & Social Sciences; and Natural & Engineering Sciences. Appendices concluding each chapter draw out key concepts, models, and techniques that are also of broader pedagogic and applied interest." "This Handbook will be of interest and use to statisticians and quantitative researchers requiring a broad overview of the applications of Bayesian Statistics, or those interested in solutions to specific problems. It will be a major reference source for teachers and students in a wide variety of fields and aims to inspire researchers to venture further into these exciting and challenging application areas."--Jacket